Modeling plasticity and dysplasia of pancreatic ductal organoids derived from human pluripotent stem cells - Breunig Markus; Merkle Jessica; Wagner Martin; Melzer Michael K; Barth Thomas F E; Engleitner Thomas; Krumm Johannes; Cohrs Christian M; Wiedenmann Sandra; Perkhofer Lukas; Jain Gaurav; Krüger Jana; et al. (2021)
Personalized in vitro models for dysplasia and carcinogenesis in the pancreas have been constrained by insufficient differentiation of human pluripotent stem cells (hPSCs) into the exocrine pancreatic lineage. Here, we differentiate hPSCs into pancreatic duct-like organoids (PDLOs) with morphological, transcriptional, proteomic, and functional characteristics of human pancreatic ducts, further maturing upon transplantation into mice. PDLOs are generated from hPSCs inducibly expressing oncogenic GNAS, KRAS, or KRAS with genetic covariance of lost CDKN2A and from induced hPSCs derived from a McCune-Albright patient. Each oncogene causes a specific growth, structural, and molecular phenotype in vitro. While transplanted PDLOs with oncogenic KRAS alone form heterogenous dysplastic lesions or cancer, KRAS with CDKN2A loss develop dedifferentiated pancreatic ductal adenocarcinomas. In contrast, transplanted PDLOs with mutant GNAS lead to intraductal papillary mucinous neoplasia-like structures. Conclusively, PDLOs enable in vitro and in vivo studies of pancreatic plasticity, dysplasia, and cancer formation from a genetically defined background.
Keywords: Biológiai tudományok; Orvos- és egészségtudomány